Environmental sustainability and economy - Singh, Pardeep; Verma, Pramit; Perrotti, Daniela; Srivastava, K. K. (Elsevier, 2021)
Environmental Sustainability and Economy contains the latest practical and theoretical concepts of sustainability science and economic growth. It includes the latest research on sustainable development, the impact of pollution due to economic activities, energy policies and consumption influencing growth and environment, waste management and recycling, circular economy, and climate change impacts on both the environment and the economy. The 21st century has seen the rise of complex and multi-dimensional pathways between different aspects of sustainability. Due to globalization, these relationships now work at varying spatiotemporal scales resulting in global and regional dynamics. This book explores the complex relationship between sustainable development and economic growth, linking the environmental and social aspects with the economic pillar of sustainable development. Utilizing global case studies and interdisciplinary perspectives, Environmental Sustainability and Economy provides a comprehensive account of sustainable development and the economics of environmental protection studies with a focus on the environmental, geographical, economic, anthropogenic and social-ecological environment.